Implementasi Manajemen Madrasah terhadap Peningkatan Mutu Pendidikan di MTs Nurul Ihsan NWDI Tanjung Luar - Eni Arnika; Kamaruddin Kamaruddin; Rosi Alpiana; Sri Hartati; Lalu Sopyan (LP2M STIT Palapa Nusantara, 2025)
Although madrasah management plays an important role in improving educational quality, studies on its planning, implementation, and impact in specific madrasah contexts still need to be strengthened. This study aims to determine the planning of madrasah management implementation and its impact on improving educational quality at MTs. Nurul Ihsan NWDI Tanjung Luar. This study used a qualitative approach. The research data sources included the madrasah principal, teachers, and parents who were involved in the process of implementing madrasah management. Data were collected through observation, interviews, and documentation, and were then analyzed qualitatively. The results showed that the implementation of madrasah management played a significant role in supporting the improvement of educational quality. The management process carried out by the madrasah principal encouraged increased trust in teachers and staff, thereby strengthening internal cooperation in efforts to improve educational quality in the madrasah. The conclusion of this study affirms that well-directed madrasah management implementation can become an important factor in strengthening educational quality. These findings imply the importance of planning, madrasah principal leadership, and collaboration among all members of the madrasah community in building a higher-quality education system.